The impact of four-week "living high-training low " on sleep and fatigue states in male rowing athletes - Shuqiang, L.; Yan, A.; Shilei, L.; Jun, Q. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The Research Objective is to explore the effects of a 4-week living high-training low regimen on rowers sleep, fatigue, and emotional states.This work is part of founding 22dz1204601,Study on exercise fatigue evaluation and recovery based on special environment. METHODS: The study involved 18 male rowing athletes, aged 19.3±2.9 years, including 2 national-level athletes, 14 first-level athletes, and 2 second-level or lower athletes. The athletes were randomly divided into a hypoxic sleep group and a control group. The hypoxic sleep group underwent a 4-week intervention with reduced oxygen levels (set at 15.8% oxygen content, equivalent to an altitude of 2500 meters) using a hypoxia generator. The control group had normal oxygen levels during sleep. Both groups followed the same training regimen. A mixed experimental design was used: 2 (hypoxic sleep group, control group) × 3 (one week before the experiment, the second week of the experiment, the fourth week of the experiment). EEG tests of 18 minutes were conducted at these three time points, followed by the Pittsburgh Sleep Quality Index (PSQI), Athletes Sleep Screening Questionnaire AIS-nca, Athlete Burnout Questionnaire ABQ, and Profile of Mood States (POMS) tests to analyze changes in various indicators. RESULTS: 1.The AIS-nca questionnaire results showed significant main effects for testing time (F=47.372, p